Oxytocin and Vasopressin, and the GABA Developmental Shift During Labor and Birth: Friends or Foes? - Ben-Ari, Yehezkel (Frontiers in Cellular Neuroscience, 2018)
Abstract Oxytocin (OT) and vasopressin (AVP) are usually associated with sociability and reduced stress for the former and antidiuretic agent associated with severe stress and pathological conditions for the latter. OT and AVP also play major roles during labor and birth. Recent studies suggest that they also might exert different roles on the GABA excitatory/inhibitory developmental shift. We reported that at birth, OT exerts a neuro-protective action mediated by an abrupt reduction of intracellular chloride levels ([Cl-]i) levels, reinforcing GABAergic inhibition and modulating the generation of the first synchronized patterns of cortical networks. This reduction of [Cl-]i levels is abolished in rodent models of Fragile X Syndrome and Autism Spectrum Disorders, and its restoration attenuates the severity of the pathological sequels, stressing the importance of the shift at birth. However, another study reported excitatory GABA actions before and after birth that are modulated by AVP, suggesting that AVP, and not OT, plays a central role during birth. Here, I analyze the differences between these studies and suggest that the ratio AVP/OT like that of excitatory/inhibitory GABA are markers of stress and pathological conditions.